2003
DOI: 10.1111/j.1582-4934.2003.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic rate in patients with myelodisplastic syndrome treated with modulatory compounds of pro‐apoptotic cytokines

Abstract: Excessive apoptosis has a central role in ineffective hematopoiesis in myelodysplastic syndrome (MDS). The aim of the study was to quantify apoptosis and Bcl‐2 expression in patients with MDS and to use these parameters in the evaluation of treatment efficacy with compounds modulating proapoptotic cytokines. Bone marrow (BM) samples from eight MDS patients were studied: four with refractory anemia and four with refractory anemia with ringed sideroblasts. Two patients with Hodgkin disease without BM determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One of the genetic factors may be an aberration of cytokine regulation and cytokine production, which can lead to an increased apoptosis of hematopoietic progenitor cells, and aberrant hematopoiesis. The excessive production of growth-inhibitory cytokines such as TNF-␣ in patients with MDS has been described [3,4,29] . Recent data indicate that TGF-␤ inhibits myeloid, erythroid, megakaryocytic and multilineage colony formation [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the genetic factors may be an aberration of cytokine regulation and cytokine production, which can lead to an increased apoptosis of hematopoietic progenitor cells, and aberrant hematopoiesis. The excessive production of growth-inhibitory cytokines such as TNF-␣ in patients with MDS has been described [3,4,29] . Recent data indicate that TGF-␤ inhibits myeloid, erythroid, megakaryocytic and multilineage colony formation [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have demonstrated an excessive production of proapoptotic cytokines in the bone marrow of MDS patients. Several studies have stressed the im portance of increased levels of tumor necrosis factor-␣ (TNF-␣ ) in the serum and bone marrow in promoting apoptosis [3,4] . Transforming growth factor-␤ (TGF-␤ ) is another cytokine which is generally considered to be a negative key regulator of hematopoietic stem and progenitor cells [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…While pro-apoptotic mechanisms are activated in HSPCs in MDS, the evolution to an aggressive AML includes a suppression of apoptosis due to changes in intracellular levels of Bcl-2-family proteins [156,143] . Nevertheless, important interactions between leukemic cells and BM microenvironment also contribute to AML progression: When natural killer cells and cytotoxic lymphocytes adhere to BM stroma, they inhibit AML blasts clonogenic growth; however, AML cells compete with them for stromal binding sites via β1 (principally VLA-4) and β2 integrins, escaping from apoptosis [70,72,157] .…”
Section: Role Of Bm Microenvironment In the Onset Of Tumorigenesis -Tmentioning
confidence: 99%
“…Other adhesion molecule patterns are modified in HSPCs from MDS and secondary AML, like ICAM-1 (overexpressed) and L-selectin (underexpressed), having prognosis importance [154] . Also, plasma levels of soluble CD44 are significantly elevated in MDS patients as compared to those of healthy donors and are increased in high-risk MDS subtypes [155] .While pro-apoptotic mechanisms are activated in HSPCs in MDS, the evolution to an aggressive AML includes a suppression of apoptosis due to changes in intracellular levels of Bcl-2-family proteins [156,143] . Nevertheless, important interactions between leukemic cells and BM microenvironment also contribute to AML progression: When natural killer cells and cytotoxic lymphocytes adhere to BM stroma, they inhibit AML blasts clonogenic growth; however, AML cells compete with them for stromal binding sites via β1 (principally VLA-4) and β2 integrins, escaping from [70,72,157] .…”
mentioning
confidence: 99%
“…Los síndromes mielodisplásicos (SMD) corresponden a un grupo heterogéneo de trastornos clonales de células madre hematopoyéticas que conducen al desarrollo de citopenias progresivas las cuales tienen un riesgo elevado de evolución hacia leucemia mieloide aguda (LMA) (1). La estratificación de dicho riesgo en combinación con los requisitos de transfusión, guían el manejo actual de SMD.…”
Section: Planteamiento Del Problema Y De La Pregunta De Investigación...unclassified